Synthesis of the C59N+ carbocation. A monomeric azafullerene isoelectronic to C60 - Kim, Kee-Chan; Hauke, Frank; Hirsch, Andreas; Boyd, Peter; Carter, Elizabeth; Armstrong, Robert; Lay, Peter; Reed, Christopher (Journal of the American Chemical Society, 2003)
A heterofullerene isoelectronic to C is reported. The azafullerenium cation CN can be isolated in good yield as a carborane salt via the two-electron oxidation of the C-C bond of (CN) dimer. [CN][Ag(CBHCl)] has been characterized by electronic, IR, Raman, and C NMR spectroscopies, MALDI spectrometry, DFT calculations, and X-ray crystallography. Copyright © 2003 American Chemical Society.